The rights of the child and the Caribbean experience: Report - UNICEF Caribbean; The University of the West Indies, Cave Hill Campus (UNICEF Caribbean Area Office, 2000)
This report summarizes the presentations made at the symposium, which was convened to: 1) invite Caribbean scholarship to examine the articulation between the articles and principles of the Convention on the Rights of the Child (CRC) and the social, historical, and cultural realities of the region; and 2) identify for policy makers in government and the civil society, central issues concerning the factors that facilitate, and those that constrain, the realization of the rights of the child.
UNICEF Caribbean Area Office in collaboration with The Department of Government, Sociology and Social Work, UWI, Cave Hill, Barbados
Keywords: child rights; Caribbean